008 BP: SYSTEMS RESILIENCE: IMPROVING PUBLIC HEALTH THROUGH COLLABORATION AND COMMUNITY BASED PARTICIPATORY RESEARCH. (3rd March 2017) - Porroche-Escudero, A; Popay, J; Barr, B; Mosedale, S; Ring, A; Sadler, G; Simpson, G; Wheeler, P
Abstract : Throughout the UK severe funding cuts are straining the capacity of local governments, National Health Service and voluntary organisations to improve public health and reduce health inequalities. At times like this, the word 'resilience' is invoked as a neoliberal mantra similar to "individual or community responsibility". Decreased public funding for services increases pressure on individuals and communities to cope with socio-economic adversity without external support. We argue that resilience must be understood in relation to systems. Promoting individual or community resilience alone is not enough to reduce health inequalities locally. Resilience needs to be understood as a characteristic of people who live and work in areas and the organisations that employ them. Enhanced resilience at a systems levels, underpinning engagement between paid workers and communities, is essential to release collective capabilities to influence and respond to structural pressures. We argue that enhanced system resilience has the potential to improve the social drivers of health inequalities and leads to improvements in collective and individual health. In this presentation we describe the experience of the public health team within the NIHR Collaboration for Leadership in Applied Health Research and Care for the North West Coast (CLAHRC NWC). We introduce a system resilience framework and describe how we are testing this in 9 relatively disadvantaged neighbourhoods in the North West of England. We discuss a number of innovative features of this work. It seeks to nurture egalitarian collaboration between residents, Local Authorities, community and organisations to understand, and influence, action that can promote system resilience. Residents conduct local enquires to help plan for action to enhance system resilience and help evaluate the impact of changes put in place.